The Estrada Plot : How the FBI Captured a Secret Army and Stopped the Invasion of Mexico - Mills, Bill, 1958- (Book collections on Project MUSE., 2020)
""The Estrada Plot" is the story of Enrique Estrada, an exiled Mexican general who organizes a secret army in California to invade Mexico and seize power. The newly formed Federal Bureau of Investigation races to uncover the plot and capture Estrada's army in time"--